ON THE RATIONAL STRUCTURE OF A ROTATING FLUID FLOW IN GEOTECHNOLOGICAL PROCESSES - Latkin A.S. (My University, 1998)
Considering the present state of the world mineral resources, it is shown that high-temperature geothermal fluids can be used to extract valuable minerals. For this purpose a technology was devised and experimental vortex equipment was built and tested under laboratory conditions. It was proved that any technological process for concentrating valuable materials (including geothermal fluids) demanded a certain vortex flow structure to optimize heat-and-mass transfer.